Exploring the incidence of culturally responsive communication in Australian healthcare: the first rapid review on this concept - Carla Minnican; Gjyn O'Toole (BMC, 2020)
Abstract Background Increasing diversity in Australia requires healthcare practitioners to consider the cultural, linguistic, religious, sexual and racial/ethnic characteristics of service users as integral components of healthcare delivery. This highlights the need for culturally appropriate communication and care. Indeed the Australian Government in various policies mandates culturally responsive communication. Therefore this paper aims to provide a brief overview of Australian healthcare literature exploring the components; prevalence and effects of this style of communication in healthcare. Methods A rapid review was conducted using the knowledge to action evidence summary approach. Articles included in the review were those reporting on the components, prevalence and outcomes of culturally responsive communication in Australian healthcare, published in English between 2008 and 2018. Articles were reviewed using reliable critical appraisal procedures. Results Twenty- six articles were included in the final review (23 qualitative studies; 2 systematic reviews; 1 mixed methods study). The literature indicates knowledge of the positive effects of culturally responsive communication in healthcare. It also highlights the disparity between the perceptions of healthcare practitioners and services users over the existence and components of culturally responsive communication in healthcare. The review identified a limited use of this style of communication, but rather a focus on barriers to culturally appropriate care, lacking an awareness of the importance of culturally responsive communication in this care. Conclusion While literature suggests the importance and positive effects of culturally responsive communication, evidence suggests inconsistent implementation of this style of communication within Australian healthcare settings. This has implications for the outcomes of healthcare for the diverse population in Australia.